2016
DOI: 10.18689/mjn-1000102
|View full text |Cite
|
Sign up to set email alerts
|

Is a flipped Classroom an effective Educational Method to meet Nursing Students Learning needs?

Abstract: Background: Due to the constantly changing environment in healthcare, nurses must be able to adjust their techniques, mind-set, and strategies to provide excellent care for their patients. Nurses are required to have the necessary skills to assess critically ill patients, provide emergent care, and identify subtle changes in health status; therefore, nurse educators must possess knowledge on current evidence-based methods that improve critical thinking and utilize active learning. The flipped classroom is a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…These results are consistent with previous results in pharmaceutical [56], dental [18], and ophthalmology [57] education. Students who are new to the flipped classroom require a certain adaptation period during which they can familiarize with and prepare to embrace this teaching method [58]. Furthermore, the results of this review showed that effects of the FC on undergraduate and higher vocational students were almost the same and that both which were better than LBL teaching.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These results are consistent with previous results in pharmaceutical [56], dental [18], and ophthalmology [57] education. Students who are new to the flipped classroom require a certain adaptation period during which they can familiarize with and prepare to embrace this teaching method [58]. Furthermore, the results of this review showed that effects of the FC on undergraduate and higher vocational students were almost the same and that both which were better than LBL teaching.…”
Section: Discussionmentioning
confidence: 89%
“…As such, the FC has been proven to effectively improve students' motivation, satisfaction, academic performance, and classroom engagement [61][62][63]. Some scholars have recognized the traditional classroom's limitations; hence, it is very important to change or improve LBL teaching, given that faculty members teaching experiences and the teaching methods that they choose influence students' learning feedback [58]. Inadequate teaching leads to low efficiency among teachers, which among teachers in students' inattention during class.…”
Section: Plos Onementioning
confidence: 99%
“…As for offline courses, most interns said that they liked the form of teacher-student interaction, and the previous article also reached a similar conclusion [ 25 ]. Although most interns thought that they could accept the FC, the students who had just come into contact with it needed a certain period of adaption, during which they could be familiar with and accept it [ 29 ]. From the FC questionnaire, we can conclude that quite a number of interns have a positive and receptive attitude towards FC, which also provides a good basis for the wider implementation of this teaching form in China in the next step.…”
Section: Discussionmentioning
confidence: 99%